NERACA BAHAN MAKANAN DAN KETERTELUSURAN KOMODITAS STRATEGIS BERAS DAN IKAN SELAR DI KOTA PALU - Safarillah, Safarillah; Laapo, Alimudin; Alamsyar, Al (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
Regional food security is highly influenced by the availability and distribution of staple foods that are stable and well-monitored. Palu City, as a food-vulnerable area, faces significant challenges in meeting community consumption needs, particularly for strategic commodities such as rice and selar fish. This study aims to analyze the availability and traceability of these strategic commodities in Palu City. A descriptive quantitative approach was used through the Food Balance Sheet (FBS) method combined with supply chain observation. The results showed that in 2024, rice availability reached 56,450 tons and selar/mackerel fish amounted to 3,420 tons. Daily per capita consumption was 399.12 grams for rice and 24.18 grams for selar fish. Rice was supplied from several surrounding districts, mainly Sigi and Parigi Moutong, while selar fish predominantly came from Parigi Moutong. This study highlights the importance of strengthening food distribution and traceability systems to ensure food security and safety in vulnerable areas like Palu City.